Penerapan Aplikasi Edmodo dalam Pembelajaran Berbasis E-learning bagi Dosen dan Mahasiswa di Poltekkes Kemenkes Padang - Alsri Windra Doni; Dewi Susanti (CV. CENDIKIA JENIUS INDONESIA, 2023)
Current advances in information technology require all universities to always keep abreast of developments, especially for the smooth running of education. One of the information technology learning media that can currently be used in lectures is Edmodo. The aim of this service is to provide an introduction and training on E-learning to lecturers and students so that they are more motivated in their lecture activities using E-learning with Edmodo as a support for teaching and learning activities at the Padang Ministry of Health Polytechnic. Implementation methods include carrying out practical activities and monitoring the use of Edmodo as an E-learning media to lecturers and students as well as providing pocket books. The results of the activity showed that all respondents (100%) stated that it was easy to access Edmodo, while motivation was still not optimal due to the unsatisfactory internet network where 66.2% rarely accessed Edmodo. Learning results for using Edmodo learning media in class A were in the high category at 30%, at the medium category at 32%, at the low category at 24% and in the very low category at 14%. The level of learning outcomes for class B students in the pass category was 78.8% (26 people) and in the incompetent category was 21.2% (7 people). The conclusion is that the ability of lecturers and students to use and utilize Edmodo in online lectures has increased.